Surgical Outcome of Amniotic Membrane Transplantation (AMT) in Patients with Corneal Ulcer in Dr. M. Djamil General Hospital, Padang, Indonesia - Rahmi Fatma Sari; Havriza Vitresia (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Amniotic Membrane Transplantation or AMT Graft has been known to successfully manage ocular surface diseases, especially corneal ulcers. The amniotic membrane promotes epithelialization and inhibits proteinase activity that is required for wound healing. A corneal ulcer is a potentially sight-threatening condition resulting in permanent corneal opacity. Methods: This is a retrospective descriptive study. Subjects were patients diagnosed with corneal ulcers and have been treated with AMT grafts. The data were grouped according to age, gender, severity, cause, visual acuity before and after AMT, and time required for complete epithelialization. Results: Fifty-two patients were included in this study, aged 41-50, with a mean age of 43,17. Men were more common than women by 88,5% vs 11,5%. AMT graft was performed for moderate and severe corneal ulcers in this study, and most of them were caused by infection. The visual acuity before AMT was mostly in the second WHO category of blindness and visual impairment. Four weeks after surgery, 34.6% of patients had improved visual acuity. Complete epithelialization was most frequently (59,6%) achieved in 15-28 days. AMT graft was repeated in 3 patients, and other surgical interventions were required for 2 patients. Conclusion: The AMT graft has successfully managed corneal ulcer patients, especially in moderate to severe cases, in Dr. M. Djamil General Hospital, Padang, Indonesia.